THE RELATIONSHIP BETWEEN KNOWLEDGE AND FAMILY SUPPORT AND COMPLIANCE WITH MEDICATION IN MENTAL DISORDER PATIENTS - Berna Detha M Nowo Dihardjo; Ferry Diana Karmilasari; Heryadi Heryadi; Heri Suroso; Mareta Deka Paraswati; Andan Liries (SYNTIFIC, 2026)
Background. Mental disorders are a form of deviant behavior patterns that occur in individuals and result in discomfort, stress pressure, body dysfunction, decreased quality of life, and their role in society. Treatment and care must be carried out continuously to prevent recurrence so that the patient can live their life. The purpose of this study was to identify the relationship between knowledge and family support with medication adherence in people with mental disorders at the Sanur health center. Research Method. This study used a cross-sectional approach. Using Kendall's Tau bivariate test. The sampling technique used was total sampling with a sample of 33 respondents. The variables are knowledge, family support, and the use of the MMAS instrument. Findings. The results of the analysis showed a relationship between knowledge and adherence to taking medication, which had a significance value of 0.044 < 0.05 and had a correlation coefficient value of 0.334. There is a relationship between family support and medication adherence, which has a significance value of 0.016 and has a correlation coefficient value of 0.407. While the closeness of the relationship shows that the variables of family support and knowledge have a correlation coefficient of 0.407, the knowledge variable has a correlation coefficient value of 0.334. Which means that the two variables have a strong, close relationship. Conclusion. There is a relationship between knowledge and family support with adherence to taking medication in people with mental disorders at the Sanur health center, Nunukan Regency, North Kalimantan.